Gallic acid induces apoptosis in human cervical epithelial cells containing human papillomavirus type 16 episomes. Issue 1 (25th June 2015) - Shi, Lin; Lei, Yanjun; Srivastava, Ranjana; Qin, Weihua; Chen, Jason J.
Abstract : The high‐risk human papillomaviruses (HPV) that infect the anogenital tract are strongly associated with the development of cervical carcinoma, which is the second most common cancer in women worldwide. Therapeutic drugs specifically targeting HPV are not available. Polyphenolic compounds have gained considerable attention because of their cytotoxic effects against a variety of cancers and certain viruses. In this study, we examined the effects of several polyphenols on cellular proliferation and death of the human cervical cancer cells and human cervical epithelial cells containing stable HPV type 16 episomes (HPVep). Our results show that three polyphenols inhibited proliferation of HeLa cells dose‐dependently. Furthermore, one of the examined polyphenols, gallic acid (GA), also inhibited the proliferation of HPVep cells and exhibited significant specificity towards HPV‐positive cells. The anti‐proliferative effect of GA on HPVep and HeLa cells was associated with apoptosis and upregulation of p53. These results suggest that GA can be a potential candidate for the development of anti‐HPV agents. J. Med. Virol. 88:127–134, 2016 . © 2015 Wiley Periodicals, Inc.